Exploring antenatal care utilization and intimate partner violence in Benin - are lives at stake? - Idriss-Wheeler, Dina (BMC Public Health, 2021)
BACKGROUND: The republic of Benin ranks in the bottom third of countries recently assessed for ANC coverage and its Ministry of Family and National Solidarity (2009) reported close to 70% of Beninese women suffered abuse at least once in their lifetime. Utilization of antenatal care (ANC) services is key to positive health outcomes for both mother and infant. This study examined the impact of intimate partner violence (IPV) on the utilization of ANC services in Benin using both the basic 4 visit model (ANC-4) and the updated WHO recommended 8-visit model (ANC-8). METHODS: Data used for this study were collected from the nationally representative 2017–2018 Benin Demographic Health Survey (BDHS) on ever-partnered women aged 15–49 who had completed both reproductive maternal health and domestic violence modules of the survey. Descriptive statistics and multivariate logistic regression analysis were performed to determine significant factors associated with ANC utilization in Benin. RESULTS: Over 40% of the women (n = 3084) reported experience of IPV in their lifetime. Findings revealed that women who ever experienced IPV (OR 0.753, 95% CI: 0.628–0.901; p = 0.002) had 25% less odds of accessing the basic four ANC visits. IPV was not found to be a factor in accessing at least eight ANC visits. With increasing number of children, there was less likelihood of accessing at least four and at least eight visits. Being in the richest quintile (OR 5.490, 95% CI 3.907–7.714; p < 0.000 for ANC-4; OR, 5.781, 95% CI: 3.208–10.41; p < 0.000), making decisions on household and health care (OR 1.279, 95% CI: 1.042–1.569 for ANC-4; OR, 1.724; 95% CI: 1.170–2.540; p = 0.006 for ANC-8), and getting paid cash for work increased the chances of utilizing ANC-four (OR 1.451, 95% CI: 1.122–1.876; 0.005) but not for ANC-eight. Belonging to the Muslim faith decreased the odds of ANC utilization compared to all other religions. CONCLUSION: This work revealed key areas for maternal health policy makers and service providers in Benin to appropriately plan effective policies (i.e., alleviate poverty; equitable health services access; cultural sensitivity) and necessary interventions (i.e. ANC education, IPV prevention, paid employment, alcohol cessation) to increase utilization of ANC. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10884-9.